2014
DOI: 10.18632/oncotarget.2156
|View full text |Cite
|
Sign up to set email alerts
|

TFF1 activates p53 through down-regulation of miR-504 in gastric cancer

Abstract: The expression of TFF1 is frequently down-regulated in human gastric cancer whereas its knockout leads to the development of gastric adenomas and carcinomas in mouse models. The molecular mechanisms underlying the TFF1 tumor suppressor functions remain unclear. In this study, we demonstrate, using colony formation assay and Annexin V staining, that reconstitution of TFF1 expression in gastric cancer cell models suppresses cell growth and promotes cell death. Furthermore, using a tumor xenograft mouse model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 48 publications
2
53
0
Order By: Relevance
“…Recently, TFF1 has been found to be able to activate p53 by downregulating miR-504 [31]. Another study has reported that TFF1 can inhibit cell proliferation by delaying G1/S cell phase transition while paradoxically increasing the expression of cyclin D1 [32].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, TFF1 has been found to be able to activate p53 by downregulating miR-504 [31]. Another study has reported that TFF1 can inhibit cell proliferation by delaying G1/S cell phase transition while paradoxically increasing the expression of cyclin D1 [32].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with a putative oncogenic role, miR-504 is overexpressed in a variety of cancers (4,(37)(38)(39)(40). However, relatively little is known about the mechanisms that control miR-504 expression, beyond its downregulation by the secreted factors CTGF and TFF1 (38,39).…”
Section: Fgf13 Depletion Augments Nucleolar Size and Increases Rrna Andmentioning
confidence: 99%
“…4, miRNAs can control cell cycle progression after DNA damage by targeting CHK1 [70][71][72][73][74], p53 [75,76], retinoblastoma 1 serine phosphates from human chromosome 3 (RBSP3) [77], cyclin D [73,78,79], CDC25a [80][81][82], p21, CDK2 [83][84][85], WEE1, PLK1, and so on. One study showed that RBSP3 is a target gene of miR-100.…”
Section: Mirnas Regulate Ddr Effectorsmentioning
confidence: 99%